HUBUNGAN RIWAYAT PAJANAN PESTISIDA DENGAN KEJADIAN DIABETES MELITUS TIPE 2 PADA PETANI PENYEMPROT DI KECAMATAN NGABLAK KABUPATEN MAGELANG - Eunike Galuh Saputri; Onny Setiani; Niki Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Diabetes mellitus type 2 is a chronic metabolic disorder disease caused by the pancreas that cannot produce enough insulin hormone or the body cannot use the existing insulin. The presence of endocrine disrupting chemical (EDC), a harmful chemical substance in the environment can cause disease and dysfunction with the natural action hormone in the human body. The prevalence of type 2 diabetes mellitus in Magelang Regency is 7.93% and make it as the highest prevalence in Central Java. This matter can cause exposure of EDC that exist in pesticide used by farmers there. The purpose of this research is to analyze the relation of history of pesticide exposure with mellitus type 2 incidents at sprayer farmer in District Ngablak, Magelang regency. This research conducted with analytical method and case control approach. The subjects were divided into two groups: case and control groups with 32 subjects in each group. The variables studied in this research are pesticide mixture type, pesticide dosage, pesticide spraying frequency, use of PPE (personal protective equipment), pesticide storage location, hand scratching habits, and years of service. The data collection is done by interview, observation, and measurement. The data analysis using univariate and bivariate analysis with chi square. The results showed that the variables associated with the incidence of diabetes mellitus type 2 was the working period, pesticide spraying frequency, use of PPE, and pesticide dosage with p value < 0,05. There is a significant relationship between the work periods, pesticide spraying frequency, use of PPE, and pesticide dosage with the incidence of diabetes mellitus type 2 as the result of the research. Expected for the farmer later when do the agricultural activities, they can use PPE (personal protective equipment) and use pesticides according to the recommended dosage.